Association of SLC6A4 gene polymorphisms with Schizophrenia - Aladzemi, Farah Wahida; Ku Zaifah, Norsidah; Abdullah, Kartini; Musa, Ramli; Abdul Razak, Tariq; Abdullah, Nor Zamzila; A.Talib, Norlelawati (2015)
Introduction: The SLC6A4 gene encode for serotonin transporter which regulates synaptic concentration of serotonin thus influences perception, mood, emotion, behavior, and cognition which are the main symptoms of Schizophrenia (Sz). This study investigated the association of SNPs within SLC6A4 gene with Sz. Methods: A total of 240 Sz patients and 364 normal controls were studied. Genomic DNA was extracted from peripheral blood. Rs12449783, rs140700, rs6352 and rs6354 were selected and genotyped using allelic discrimination real time Taqman® assay. Results: A significant association was found between rs12449783 of SLC6A4 gene and Sz for both alleles and genotypic frequencies (p = 1.68 x 10−8 and 5.11 x 10−7 respectively). Conclusion: The significant association between rs12449783 of SLC6A4 gene in our Sz samples reaffirmed the previous similar findings in other population thus support role of SLCA4 gene in Sz.